2023
DOI: 10.1073/pnas.2308516120
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and temperature drive diurnal variation of aerobic methane emissions from Scots pine canopy

Lukas Kohl,
Salla A. M. Tenhovirta,
Markku Koskinen
et al.

Abstract: Methane emissions from plant foliage may play an important role in the global methane cycle, but their size and the underlying source processes remain poorly understood. Here, we quantify methane fluxes from the shoots of Scots pine trees, a dominant tree species in boreal forests, to identify source processes and environmental drivers, and we evaluate whether these fluxes can be constrained at the ecosystem-level by eddy covariance flux measurements. We show that shoot-level measurements conducted in forest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In these ecosystems, methane exchange has been more difficult to disentangle chiefly due to the difficulty of making in situ measurements of very small fluxes, in either direction, and identifying their source from a range of processes at scale and from within relatively inaccessible (for chamber measurement campaigns) tree crowns and canopies. These sources include aerobic sources that have wide uncertainties (Keppler et al 2006, Kohl et al 2023. However, in Gauci et al (2024), woody stem surfaces of upland trees were shown to be a significant locus of atmospheric methane removal (AMR), potentially as large or larger than the well-understood global soil sink (Dunfield 2007).…”
mentioning
confidence: 99%
“…In these ecosystems, methane exchange has been more difficult to disentangle chiefly due to the difficulty of making in situ measurements of very small fluxes, in either direction, and identifying their source from a range of processes at scale and from within relatively inaccessible (for chamber measurement campaigns) tree crowns and canopies. These sources include aerobic sources that have wide uncertainties (Keppler et al 2006, Kohl et al 2023. However, in Gauci et al (2024), woody stem surfaces of upland trees were shown to be a significant locus of atmospheric methane removal (AMR), potentially as large or larger than the well-understood global soil sink (Dunfield 2007).…”
mentioning
confidence: 99%